Pengaruh Kualitas Pelayanan terhadap Kepuasan Pelanggan Di PT Hutchison 3 Indonesia - Abadi Siregar, Mayer (Journal of Economics & Business UBS, 2020)
Quality of service to customers has a very important role. PT Hutchison Tri Indonesia which is engaged in telecommunication services, hence to improve the quality of management services form for 3Store, the application of the new concept is still not sure whether it can improve the quality of service or vice versa. With very different concepts raises the pros and cons of customers. The problem to be studied is "Whether the quality of service affect the customer satisfaction on 3Store Ambasador in terms of the five variables of service quality which are: physical evidence, reliability, assurance, responsiveness, and empathy. The purpose of this study is to determine the quality of service with new concepts affecting customer satisfaction of 3Store Ambasador. Hypothesis in this study quality of service consisting of physical evidence variables, reliability, assurance, responsiveness, and empathy have a significant effect on customer satisfaction 3Store Ambasador. Methods of data collection to test the hypothesis using a questionnaire addressed to 100 respondents 3Store Ambasador customers. Based on t-test results, each independent variable that is physical evidence, reliability, responsiveness, assurance, and empathy have a positive effect on the variable (Y) customer satisfaction, the most influential is the guarantee variable, the conclusion of the numberd hypothesis rejected and the hypothesis of null received.